(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyse elementary school students’ interest in improving volleyball achievement in the Cimanggung District. The method used is a quantitative descriptive method with a survey technique, utilising a questionnaire as the main instrument. The research sample consists of 100 fifth and sixth-grade students from several elementary schools in the area. The data were analysed using descriptive statistics in the form of percentages and average values. The results of the study show that students’ overall interest in volleyball is in the high category, with 80% of students showing high interest and 20% falling into the moderate category. The most dominant intrinsic factor influencing students’ interest is their curiosity and attention toward volleyball, while extrinsic factors such as the role of teachers and available facilities also have an influence, albeit to a lesser extent. The study concludes that high student interest can positively contribute to improved achievement in volleyball. Therefore, support from the school environment, engaging learning strategies, and adequate facilities are crucial to maintaining and enhancing students’ interest in this sport.